Doxorubicin-loaded magnetic gold nanoshells for a combination therapy of hyperthermia and drug delivery - Mohammad, Faruq; Yusof, Nor Azah (Elsevier, 2014)
In the present work, nanohybrid of an anticancer drug, doxorubicin (Dox) loaded gold-coated superparamagnetic iron oxide nanoparticles (SPIONs@Au) were prepared for a combination therapy of cancer by means of both hyperthermia and drug delivery. The Dox molecules were conjugated to SPIONs@Au nanoparticles with the help of cysteamine (Cyst) as a non-covalent space linker and the Dox loading efficiency was investigated to be as high as 0.32 mg/mg. Thus synthesized particles were characterized by HRTEM, UV–Vis, FT-IR, SQUID magnetic studies and further tested for heat and drug release at low frequency oscillatory magnetic fields. The hyperthermia studies investigated to be strongly influenced by the applied frequency and the solvents used. The Dox delivery studies indicated that the drug release efficacy is strongly improved by maintaining the acidic pH conditions and the oscillatory magnetic fields, i.e. an enhancement in the Dox release was observed from the oscillation of particles due to the applied frequency, and is not effected by heating of the solution. Finally, the in vitro cell viability and proliferation studies were conducted using two different immortalized cell lines containing a cancerous (MCF-7 breast cancer) and non-cancerous H9c2 cardiac cell type.